2009
DOI: 10.2353/ajpath.2009.090246
|View full text |Cite
|
Sign up to set email alerts
|

The Metastasis-Associated Anterior Gradient 2 Protein Is Correlated with Poor Survival of Breast Cancer Patients

Abstract: The secreted metastasis-inducing protein, human anterior gradient 2 (AGR2), has been independently reported to be associated with either a reduced or an increased survival of different groups of patients with breast cancer. We now aim to analyze the expression of AGR2 in a third completely independent group of patients using a specific AGR2 monoclonal antibody (mAb). Primary tumors from a group of 315 patients suffering from operable (stage I and II) breast cancer with 20-years follow-up were immunocytochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(95 citation statements)
references
References 28 publications
5
89
1
Order By: Relevance
“…Increased AGR2 expression has previously been shown to be associated with metastasis and a poor prognosis in breast cancer patients (Barraclough et al 2009), and to correlate with high-grade serous carcinoma and shortened overall survival of ovarian cancer patients (Innes et al 2006). In addition to the tumor-promoting roles of AGR2, tamoxifen-induced AGR2 expression has also been implicated in the development of resistance of tumors against tamoxifen and cisplatin treatments (Hrstka et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Increased AGR2 expression has previously been shown to be associated with metastasis and a poor prognosis in breast cancer patients (Barraclough et al 2009), and to correlate with high-grade serous carcinoma and shortened overall survival of ovarian cancer patients (Innes et al 2006). In addition to the tumor-promoting roles of AGR2, tamoxifen-induced AGR2 expression has also been implicated in the development of resistance of tumors against tamoxifen and cisplatin treatments (Hrstka et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Overall patient survival and the significant pathological prognostic variables over 20 years have been summarized recently. 1 …”
Section: Patients and Specimensmentioning
confidence: 99%
“…1,27,28 These and the malignant epithelial cell lines derived from pleural effusions of breast cancer patients MCF-7, T47D, MDA-MB-157, and MDA-MB-231 were cultured as described 27 ; the MCF-7 and T47D were relatively noninvasive (low invasive), and MDA-MB-157 and MDA-MB-231 were highly invasive (high invasive). 29 MDA-MB-157-FANCD2 was generated by transducing MDA-MB-157 cells with a retroviral supernatant of a wild-type FANCD2 cDNA pMMP construct 30 and subsequent selection in puromycin as previously described.…”
Section: Cell Lines and Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…A more recent study using patients that have only undergone operative breast cancer surgery indicated that high AGR2 expression is linked to poor survival (Barraclough et al, 2009). Therefore, the precise function of these proteins and the mechanisms of their hormonal regulation in breast cancers remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%